UNDERSTANDING THE INFLUENCE OF SOCIAL DETERMINANTS OF HEALTH ON EXCLUSIVE BREASTFEEDING AT DISCHARGE FROM THE HOSPITAL - (:unkn) unknown (My University, 2023)
Background: US women are not meeting the breastfeeding exclusivity and duration goals recommended by clinical and public health experts. The 2020 Breastfeeding Report Card from the Center for Disease Control states that 84.1% of infants are ever breastfed in the United States and 19.2% will receive formula supplementation within the first two days of life. It is unknown which Social Determinants of Health (SDOH) can influence breastfeeding exclusivity at discharge from the hospital.
Methods: The study was a retrospective secondary analysis of a single institution utilizing the PeriData.Net™ data set. This descriptive correlational study used the SDOH framework to explore the relationship of which variables can influence exclusive breastfeeding at discharge.
Results: 6939 birth persons were included in the study. Several SDOH factors; maternal age, maternal country of birth, prepregnancy depression, maternal zip code and BMI demonstrated a significant (p<.05) with exclusive breastfeeding at discharge from the hospital. The logistic regression model showed that prenatal depression and country of birth continued to demonstrate a relationship on exclusive breastfeeding at discharge from the hospital.
Conclusions: This study used a data set from a single hospital that provided an opportunity to understand the relationship of the variables that included maternal factors, SDOH factors and perinatal factors with exclusive breastfeeding at discharge from the hospital. In this study, there were several statistically significant relationships identified that influence exclusive breastfeeding at discharge. In this model prepregnancy depression and country of birth that continued to demonstrate a relationship on exclusive breastfeeding at discharge from the hospital.
Keywords: breastfeeding; PeriData.Net™; prepregnancy; SDOH